Efektivitas ekstrak kunyit (Curcuma longa) sebagai bioinsektisida alami untuk menghalau lalat rumah (Musca domestica) - Wiwit Aditama; Zulfikar Zulfikar; Khairunnisa Khairunnisa; Budi Arianto (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Fly-borne diseases are still a health problem in urban and rural communities, such as diseases related to the gastrointestinal tract, such as abdominal typhus, cholera, typhoid fever, diarrhoea, dysentery, and others. The simplest and most common mode of transmission is mechanical. In this method, the vector spreads the parasite through contact with the host without the parasite breeding on the fly.Objectives: This study aimed to determine the effectiveness of turmeric extract (Curcuma longa) as a natural bioinsecticide to repel house flies (Musca domestica).Method: Quasi-experiment with only design with control design. The samples in this study were 20 houseflies in each of the two treatments and one control with three repetitions. The research was conducted at the Aceh Polytechnic Laboratory in 2022 and analyzed by ANOVA test at 95% CI.Result: It was found that the number of houseflies that rejected the administration of turmeric extract was 28, based on concentrations of 10gram/100ml, 15gram, 100ml and control (without adding extracts).At the concentration of control - 10gram/100ml (p= 0,005), 10gram/100ml - 15gram/100ml (p= 0,000), control - 15gram/100ml. There is a significant difference in each concentration (p = 0,000).Conclusion: Turmeric extract, as a natural bioinsecticide for house fly repellent, is most effective at a concentration of 15 grams/100 ml. It is suggested that the community can utilize turmeric extract can be recommended as a bio-insecticide and a house fly repellent in the household industry process.